The Internationalisation of Regions: Paradiplomacy or Multi‐level Governance?. Issue 10 (October 2014) - Dickson, Francesca
Abstract This article reviews the two primary frameworks used to explore the external relations of regions. It argues that the concepts of multi‐level governance and paradiplomacy are used to describe similar, but distinct, international activities on the part of regions and sub‐state governments. Both approaches look at the ways in which regions engage beyond the local level, and increasingly so. The inevitable overlap between their subject matter has meant that the two terms are sometimes used interchangeably, leading to a mischaracterisation of the practices themselves. The international mobilisation of regions manifests in numerous modes, and therefore much greater specificity is required in analysing and interpreting these varied phenomena. In particular, the novelty of paradiplomacy, and the political contestation that it can imply, risks being under‐reported. Firmer boundaries between the two approaches, and a better conceptualisation of the relationship between them, are called for in this interdisciplinary review. The article argues that where multi‐level governance presents a predominately structural account of 'governance' based activities, paradiplomacy has the potential to provide an agency‐oriented explanation of autonomous, diplomatic practices – often with deeply political connotations. It is suggested that the two can represent parallel, alternative or complementary approaches, depending on the exact nature of the activity under consideration. It concludes by suggesting future avenues for paradiplomatic research.